Finger millet-based staple beverages consumed by the Gadaba ethnic community of Odisha, India: Preparation and nutritive characteristics - ARUP KUMAR MISHRA; RANJANA BAJPAI; AMRITA SWAIN (Society for Indonesian Biodiversity, 2021)
Abstract. Mishra AK, Bajpai R, Swain A. 2021. Finger millet-based staple beverages consumed by the Gadaba ethnic community of Odisha, India: Preparation and nutritive characteristics. Biodiversitas 22: 2737-2742. The indigenous food and beverages reflect the acquaintance of ethnic population to local environmental settings. Development of diet structure includes diversities in food and beverages depend on the ethnic knowledge they perceive from their ancestors as well as from the environmental determinants. The Gadaba ethnic community being native to the southern part of Odisha state in India, developed the art to sustain them through rain-fed agricultural crops like finger millet and upland rice. These traditional non-hybrid crops give different dimensions to their food and beverage structure. In this case, the study focussed on finger millet-based staple beverages consumed by Gadaba ethnic community of this region. The effort is given to discuss the complete indigenous preparation process and nutritional parameters concerning two indigenous indispensable fermented beverages named Landa and Pej. The nutritional analysis of these beverages proved it to be a promising diet structure for sustainability.